Peripheral arterial systolic-diastolic velocities in athletes and non-athletes by doppler ultrasound - Mateus, Sónia (2019)
Submitted by Patricia Coelho (patriciacoelho@ipcb.pt) on 2019-10-20T23:29:26Z No. of bitstreams: 1 peripheral.pdf: 127929 bytes, checksum: 4b0c384801db825ca09359824540093c (MD5)